The Analysis of Socialist Thought in the Perspective of Vladimir Lenin - Mahayano, Bounpheng (Journal of Graduate MCU KhonKaen Campus, 2025)
This research entitled “An Analysis of Socialist Thought in the Perspective of Vladimir Ilyich Lenin” aimed to: 1) study the concept of socialism, 2) examine socialist thought in the perspective of Vladimir Ilyich Lenin, and 3) analyze Lenin’s socialist thought. This study employed documentary research methodology by collecting data from primary sources, including the works of Vladimir Ilyich Lenin, and secondary sources such as books, academic articles, and related research studies. The data were analyzed through content analysis and descriptive-inductive interpretation. The findings revealed that: 1) socialism is a socio-political ideology aimed at establishing economic and social equality through the fair distribution of resources, the reduction of exploitation, and the elimination of class inequality 2) Lenin’s socialist thought was developed from Karl Marx’s theoretical framework and adapted to the socio-political context of Russia, emphasizing the role of the vanguard party, the dictatorship of the proletariat, and the struggle against imperialism as essential mechanisms for achieving a socialist society 3) Lenin’s socialist thought sought to promote equality and social justice through political participation, state control of the means of production, and equitable distribution of resources for the common good. Moreover, Lenin’s ideas significantly influenced the political and economic development of socialist states and continue to be an important subject in contemporary social and political philosophy.